Leveraging Artificial Intelligence to Improve English Speaking Skill Among Students: A Comprehensive Study - Boedy Irhadtanto; Eddy Sutadji (IKIP PGRI Bojonegoro, 2024)
This journal investigates the linguistic challenges faced by students despite years of English language education, spanning three years in junior high school, three years in senior high school, and over four years in tertiary education. While students demonstrate comprehension skills in English listening, they encounter difficulties in verbal expression. This research employs a literature review methodology to explore the underlying factors contributing to this issue and proposes effective strategies, including the integration of Artificial Intelligence (AI), to augment English speaking proficiency.